2017
DOI: 10.18240/ijo.2017.05.23
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors among children, adolescents and adults attending eye clinics in Mexico

Abstract: Myopia is the most common refractive error in the population studied. This study provides the first data on refractive error in Mexico. Further programs and studies must be developed to address the refractive errors needs of the Mexican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 23 publications
8
26
1
Order By: Relevance
“…This is agreement with the prevalence of hyperopia in this age group in the Gomez-Salazar et al 16 study. In keeping with the hyperopic shift known to occur in older people, [28][29][30] hyperopia increased to 34% in participants over 40, a similar prevalence to that reported in Mexican patients by Gomez-Salazar et al 16 Prevalence of hyperopia in people over 40 has been reported to be 25% in population based studies in the US and Europe. 13,19…”
Section: Prevalence Of Hyperopiasupporting
confidence: 92%
See 4 more Smart Citations
“…This is agreement with the prevalence of hyperopia in this age group in the Gomez-Salazar et al 16 study. In keeping with the hyperopic shift known to occur in older people, [28][29][30] hyperopia increased to 34% in participants over 40, a similar prevalence to that reported in Mexican patients by Gomez-Salazar et al 16 Prevalence of hyperopia in people over 40 has been reported to be 25% in population based studies in the US and Europe. 13,19…”
Section: Prevalence Of Hyperopiasupporting
confidence: 92%
“…20 The relatively low prevalence of myopia among children and young adults from the Tijauna neighborhoods who attended our clinics is of interest. In the Gomez-Salazar et al 16 report, 20% of children 6-9 years old and 41% of those 10-19 years old were myopic. The Gomez-Salazar study may be compared to the present study, because the patients were self-selected, based on a decision to be examined at an optometry clinic.…”
Section: Prevalence Of Myopiamentioning
confidence: 93%
See 3 more Smart Citations